The violation of the rights of slaves in Roman law - kebayli, kahina (Journal of Social Sciences and Humanities, 2023)
Slavery is a system that permits man to exploit his fellow man for economic and social purposes, and this system was common in ancient societies and has continued to this day with taking multiple and different forms, and its characteristics varied from one society to another. However, the common characteristic between these societies has remained the same through all times , which is the stripping of the slave of all his personal and civil rights, as he was relegated to the bottom of social class and they turned into a mere commodity sold and bought like all other pets. In order to ensure the continuity of this system, it was necessary to issue legal provisions to protect the right of the master owner and to provide guarantees to preserve his property. Thus, the slave became at the mercy of his master, who was given all powers by law, including the right to life and death, therefore, their situation depended on the nature of their master's temperament.